Reimagining Western Femininity Through Ellie in The Last of Us and The Last of Us: Left Behind - Catarina Ricardo (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
Women in the Western genre have conventionally been assigned roles in which they are subordinated to the male hero’s journey, acting as civilizers, love interests, or sexual objects. This article argues that Ellie in The Last of Us (2013) and its subsequent DLC, The Last of Us: Left Behind (2014), stands out as a remarkably transgressive character when compared to the archetypal representations of women in Westerns. Acknowledging the video game as a Weird Western, this article analyzes several aspects of its narrative and gameplay in which subversion becomes evident, focusing in particular on the plot, game mechanics, and character design. Firstly, the overturning of the classical female role is made possible through the masculinization of Ellie, who temporarily becomes a playable protagonist, assuming the place of the cowboy in all his autonomous resilience: hunting animals and killing enemies who endanger Joel. Ellie’s killing of David sets her apart from the expected female behavior by demonstrating her self-sufficiency and the futility of relying on a savior. Furthermore, her queerness is presented to the player as an inherent trait, challenging the virtually compulsory heterosexuality of the Western. Nonetheless, this portrayal is not without its limitations. As this paper argues, the ending of the game empowers Joel at Ellie’s expense, ultimately upholding familiar tropes that glorify patriarchal authority. Thus, while Ellie is unquestionably a revolutionary female character, traces of tradition still seep into the contemporary (Weird) Western.